Combined neuromodulatory interventions in acute experimental pain: assessment of melatonin and non-invasive brain stimulation - da Silva, Nádia Regina Jardim; Laste, Gabriela; Deitos, Alícia; Stefani, Luciana Cadore; Cambraia-Canto, Gustavo; Torres, Iraci L. S.; Brunoni, Andre R.; Fregni, Felipe; Caumo, Wolnei (Frontiers in Behavioral Neuroscience, 2015)
Transcranial direct current stimulation (tDCS) and melatonin can effectively treat pain. Given their potentially complementary mechanisms of action, their combination could have a synergistic effect. Thus, we tested the hypothesis that compared to the control condition and melatonin alone, tDCS combined with melatonin would have a greater effect on pain modulatory effect, as assessed by quantitative sensory testing (QST) and by the pain level during the Conditional Pain Modulation (CPM)-task. Furthermore, the combined treatment would have a greater cortical excitability effect as indicated by the transcranial magnetic stimulation (TMS) and on the serum BDNF level. Healthy males (n=20), (aged 18 to 40 years), in a blinded, placebo-controlled, crossover, clinical trial, were randomized into three groups: sublingual melatonin (0.25 mg/kg)+ a-tDCS, melatonin (0.25 mg/kg)+sham-(s)-tDCS, or sublingual placebo+s-tDCS. Anodal stimulation (2 mA, 20 min) was applied over the primary motor cortex. There was a significant difference in the heat pain threshold (°C) for melatonin+a-tDCS vs. placebo+s-tDCS (mean difference: 4.86, 95% confidence interval [CI]: 0.9 to 8.63) and melatonin+s-tDCS vs. placebo+s-tDCS (mean: 5.16, 95% CI: 0.84 to 8.36). There was no difference between melatonin+s-tDCS and melatonin+a-tDCS (mean difference: 0.29, 95% CI: −3.72 to 4.23). The mean change from the baseline on amplitude of motor evocate potential (MEP) was significantly higher in the melatonin+a-tDCS (−19.96%±5.2) compared with melatonin+s-tDCS group (−1.36%±5.35) and with placebo+s-tDCS group (3.61%±10.48), respectively (P<0.05 for both comparisons). While melatonin alone or combined with a-tDCS did not significantly affect CPM task result, and serum BDNF level. The melatonin effectively reduced pain; however, its association with a-tDCS did not present an additional modulatory effect on acute induced pain.